In the Company of the Unknown: Cultivating Curiosity for Ecological Renewal - Dragana Favre (Challenges, 2025)
This article argues that environmental education must move beyond knowledge transmission to become a transformative, psychological, and relational practice. Rooted in the One Health framework, which emphasizes the interconnectedness of human, animal, and ecological well-being, this article positions curiosity as a central catalyst for ecological and psychological integration. While this article specifically engages with the One Health framework, the same integrative principles apply equally to the closely related Planetary Health perspective, emphasizing interconnected human, ecological, and planetary well-being. Drawing from Jungian and post-Jungian psychology, ecopsychology, and educational theory, it redefines curiosity as a symbolic, ethical, and affective mode of engagement with the Other, both within the psyche and in the more-than-human world. Through boredom, dialogue, narrative, and embodied practices, curiosity creates space for inner movement, narrative reconfiguration, and a relational mode of knowing that can confront ecological crises with imagination, patience, and integrity. This article offers pedagogical strategies to cultivate this deeper form of curiosity as a foundation for lifelong ecological engagement.